2017
DOI: 10.3390/cells6010006
|View full text |Cite
|
Sign up to set email alerts
|

Invariant Chain Complexes and Clusters as Platforms for MIF Signaling

Abstract: Invariant chain (Ii/CD74) has been identified as a surface receptor for migration inhibitory factor (MIF). Most cells that express Ii also synthesize major histocompatibility complex class II (MHC II) molecules, which depend on Ii as a chaperone and a targeting factor. The assembly of nonameric complexes consisting of one Ii trimer and three MHC II molecules (each of which is a heterodimer) has been regarded as a prerequisite for efficient delivery to the cell surface. Due to rapid endocytosis, however, only l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 131 publications
1
16
0
Order By: Relevance
“…The observation of intracellular complexes of Ag-BCR and MHC class II is also in line with the 2014 report of Hauser and Lindner, who demonstrated that under some conditions, cell surface Ag-BCR complexes and Ii-class II complexes can coalesce in the same membrane micro-domains [63, 64]. This coalescence requires both antigen-driven BCR cross-linking as well as Ii-MHC crosslinking by molecules such as MIF ( m igration i nhibition f actor, an Ii ligand [63, 64]). While it is currently unclear how frequently the required level of Ii-class II crosslinking would occur in vivo , the finding does demonstrate the propensity of emergent MHC class II molecules to associate with at least one source of antigenic peptides (i.e., Ag-BCR complexes) in a putative MHC class II PLC.…”
Section: Formation Of Peptide–class II Complexes: An Mhc Class Ii Pepsupporting
confidence: 85%
“…The observation of intracellular complexes of Ag-BCR and MHC class II is also in line with the 2014 report of Hauser and Lindner, who demonstrated that under some conditions, cell surface Ag-BCR complexes and Ii-class II complexes can coalesce in the same membrane micro-domains [63, 64]. This coalescence requires both antigen-driven BCR cross-linking as well as Ii-MHC crosslinking by molecules such as MIF ( m igration i nhibition f actor, an Ii ligand [63, 64]). While it is currently unclear how frequently the required level of Ii-class II crosslinking would occur in vivo , the finding does demonstrate the propensity of emergent MHC class II molecules to associate with at least one source of antigenic peptides (i.e., Ag-BCR complexes) in a putative MHC class II PLC.…”
Section: Formation Of Peptide–class II Complexes: An Mhc Class Ii Pepsupporting
confidence: 85%
“…21 Cell surface-expressed CD74 can form either homodimers or heterodimers with other cell surface receptors, namely, CD44 or Chemokine receptor-2/Chemokine receptor-4 (CXCR2/CXCR), to form a molecular complex capable of eliciting cellular signaling responses. 22,23 Although Veillat and colleagues 10 have demonstrated using in vitro stromal cell cultures that CD74 (along with CD44) mediates MIF induction of factors proposed to contribute to the pathophysiology of endometriosis, there is little to no knowledge on the expression of CD74 in human endometriotic lesion tissue. As such, the objective of this study was to examine CD74 expression in endometriotic lesion tissue and to incorporate in vivo and in vitro models to further understand the role of this MIF receptor in endometriosis pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…This study focused on two lysosomal cathepsins, S and C, which are both members of the papain-like superfamily of cysteine proteases (Turk et al, 2012 ; Rawlings et al, 2016 ). The first target, cathepsin S, is involved in the crucial step in the processing of major histocompatibility complex class II (MHC II)-associated chaperone invariant chain (Roche and Furuta, 2015 ; Lindner, 2017 ), as well as being involved in the lysosome-mediated response to microbial DNA via the TLR9 pathway (Matsumoto et al, 2008 ). The second target, cathepsin C, is an exoprotease, the function of which in human DC is not yet fully known.…”
Section: Introductionmentioning
confidence: 99%